2017
DOI: 10.1097/md.0000000000007158
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of single nucleotide polymorphisms of CRYAA and CRYAB genes with the risk and clinicopathological features of children suffering from congenital cataract

Abstract: Background:The study aims to explore the correlations of the single nucleotide polymorphisms (SNPs) of CRYAA and CRYAB with the risk and clinicopathological features of children with congenital cataract.Methods:The study enrolled 168 children diagnosed as congenital cataract (case group) and 172 normal children (control group) from May 2015 to May 2016. Genomic DNA extraction was performed using a QIAamp DNA blood mini kit. Polymerase chain reaction (PCR) products were genotyped using an ABI direct sequencer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[ 1 ] Both disorders occur either in isolation or as part of a syndrome and are highly heterogeneous. [ 1 4 ] Several chromosomal, monogenic, and environmental factors have been identified as causes for the occurrence of congenital cataract and microphthalmia. [ 1 5 6 ] Nevertheless, genetic causes have been suggested to play a major role in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Both disorders occur either in isolation or as part of a syndrome and are highly heterogeneous. [ 1 4 ] Several chromosomal, monogenic, and environmental factors have been identified as causes for the occurrence of congenital cataract and microphthalmia. [ 1 5 6 ] Nevertheless, genetic causes have been suggested to play a major role in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Although the majority of mutations that were identified till date in human congenital cataract is in crystallin genes,[ 17 ] only a few studies have reported the association of intronic SNPs of crystallin genes with congenital cataract. [ 15 21 22 23 ] Furthermore, all these studies have been performed in different ethnic groups and different cohorts of the Indian population. In all these studies, the population from the western region of India was always kept isolated.…”
mentioning
confidence: 99%